Review: Biotechnology of mycotoxins detoxification using microorganisms and enzymes - Ben Taheur, Fadia; Kouidhi, Bochra; Al Qurashi, Yasir Mohammed A.; Ben Salah-Abbès, Jalila; Chaieb, Kamel (Toxicon (Oxford), 2019)
Mycotoxins are secondary metabolites produced by various toxigenic fungi belonging to the genera Aspergillus, Fusarium and Penicillium. They have mutagenic, teratogenic, carcinogenic, immunosuppressive and endocrine disrupting effects on both humans and animals. The ubiquitous occurrence and heat stability of these mycotoxins during food and feed processing pose serious health problems in human and animals. Therefore successful biotechnological detoxification tools are in great demand. Recently, the use of bacteria, yeast, moulds and enzymes to mitigate/bind or biodegrade various mycotoxins is a novel strategy used for mycotoxins removal. In this review, recent development in biological control of mycotoxins removal and detoxification will be discussed. •Mycotoxins are secondary metabolites produced by Aspergillus, Fusarium and Penicillium.•Mycotoxins have mutagenic, teratogenic, carcinogenic effects on both humans and animals.•Bacteria, yeast and moulds may be used as a novel strategy for mycotoxins removal.